Pengaruh Kecerdasan Emosional terhadap Prestasi Belajar Matematika Peserta Didik Kelas V SDN Rambutan 03 Pagi - Nida Hanifah; Rudy Gunawan (LP. Ma'arif Janggan Magetan, 2023)
This research aims to determine whether or not there is a positive influence between emotional intelligence on the mathematics learning achievement of class V students at SDN Rambutan 03 Pagi, East Jakarta. This research is ex-post facto research. This research is quantitative research. The variables in this research are the independent variable (emotional intelligence) and the dependent variable (learning achievement). Use of documentation data such as the average score of students' report cards and the emotional intelligence scale as a data collection method. This research uses data analysis techniques in the form of simple linear regression analysis. The research results showed that the R Square (coefficient of determination) was 0.051 or in percent form 5.1%. Based on the results, the contribution of variable X to Y is 5.1% while the remaining 94.9% is based on other factors. These factors can be external factors (originating from outside a person) or internal factors (originating from within a person). The influence of emotional intelligence on participants' learning achievement has a regression equation, namely Y = 61.835 + 0.296, which means that every increase in emotional intelligence by one value can reduce the learning achievement value by 0.296. It was concluded that emotional intelligence greatly influences the mathematics learning achievement of class V students at SDN Rambutan 03 Pagi.